Trends in Primary Antibiotic Resistance in H. pylori Strains Isolated in Italy between 2009 and 2019 - Ilaria Maria Saracino; Giulia Fiorini; Angelo Zullo; Matteo Pavoni; Laura Saccomanno; Dino Vaira (MDPI AG, 2020)
Background and aims: the increasing prevalence of strains resistant to antimicrobial agents is a critical issue for the management of Helicobacter pylori infection. This study aimed to evaluate, in Italian naïve patients, H. pylori antibiotic resistance trends and their potential predictive factors during the last decade. Methods: consecutive Italian naïve H. pylori positive patients, referred from General Practitioners to our Unit from January 2009 to January 2019 to perform an upper gastrointestinal endoscopy (UGIE), were considered. Each patient underwent 13C-urea breath test (13C-UBT) and UGIE with multiple biopsies to perform rapid urease test (RUT), culture/susceptibility test (vs. clarithromycin, metronidazole, levofloxacin), and histopathological examination. H. pylori status was assessed through CRM (composite reference method: at least two tests positive or only culture positive). Results: between 2009 and 2014, 1763 patients were diagnosed as H. pylori positive, 907 were naïve with antibiogram available. Between 2015 and 2019, 1415 patients were diagnosed as H. pylori positive, antibiotic susceptibility test was available in 739 naïve patients. H. pylori primary antibiotic resistance rates in the first and second five-year period were, respectively, clarithromycin 30.2% (95% CI 27.2−33.3), 37.8% (95% CI 34.2−41.4); metronidazole 33.3% (95% CI 30.2−36.5), 33.6% (95% CI 30.2−37.1); levofloxacin 25.6% (95% CI 22.8−28.5), 33.8% (95% CI 37.4−47.4), double resistance clarithromycin-metronidazole 18.9% (95% CI 16.4−21.6), 20.7% (95% CI 17.8−23.8). The increase of the resistance rates to clarithromycin and levofloxacin in naïve patients was statistically significant (p < 0.05). Although eradication rates for sequential therapy in the 10 years considered were 93.4% (95% CI 92−94.6) and 87.5% (95% CI 85.7−89) at per-protocol (PP) and intention-to-treat (ITT) analysis, respectively, they showed a significant decrease in the second five-year period. Conclusions: this data highlights an increase in primary H. pylori antibiotic resistance and strongly suggests the importance of drug susceptibility testing also in naïve patients.